Developmental Testing of Prototype Dental Model for Teachers to Practice Tooth Brushing of Primary School Students - Sriviriyakul, Supannee (Journal of Health Science of Thailand, 2017)
Clean tooth brushing can prevent dental caries and gingivitis. Primary school students have both deciduous and permanent teeth. Demonstration of tooth brushing with big permanent teeth dental model is unable to make students understand how to brush properly. Tooth brushing practise should use Inixed dentition dental model. This study aimed to produce and test efficiency of a prototype dental model that teachers could use to practice tooth brushing for their students. A primary school in Nonthaburi was approached to be the study site. One student was randomly selected from each grade (1 - 6 grade) to Participate the study which began by an invention of a prototype dental model from the volunteer students. Practice of tooth brushings was observed. As for the results, the efficiency of single and group tooth brushing practises was calculated to be 80.00% and 78.0% respectively. The students were found to be Satisfied with tooth brushing practise using the prototype dental model. Therefore, the mixed dentition dental model should be promoted and distributed to schools so that teachers could teach tooth brushing with this model among the third and fourth grade primary school students. It could be expected that such teaching and practising could reduce dental caries and gingivitis in the fifth grade students and beyond.